Transformasi Bisnis dengan Etika Bisnis Islam: Keadilan dan Tanggung Jawab dalam Ekonomi Syariah - Maulena, Maulena; Zulkarnain, Teuku; Mariana, Mariana (Universitas Jabal Ghafur, 2024)
This study analyzes the application of the principles of justice and responsibility in Islamic economics, as well as the role of Islamic business ethics in creating fair and sustainable businesses. The focus of this research is to understand how Islamic principles such as justice, transparency, and social responsibility are applied in modern businesses and their impact on business sustainability and community welfare. The research method used is descriptive qualitative with a normative legal approach, relying on literature review as the data collection technique. The collected data is analyzed to gain an understanding of business principles that align with Islamic values. The findings indicate that the application of the principle of justice in Islamic economics is not only related to wealth distribution but also to ensuring that transactions are fair and do not harm any party. Social responsibility includes obligations to ensure employee welfare, provide halal products, and minimize negative impacts on society and the environment. Despite challenges in implementation, the growing awareness of the importance of Islamic business ethics and social responsibility provides opportunities to strengthen business sustainability. This study emphasizes the importance of integrating Islamic principles into business operations and the need for government regulations that support Islamic economics and education on Islamic-based business ethics.